The creative spirit of an universal totality in ideal intentions of social life (Actual Problems of Mind, 2017)
The paper elaborates a socio-cultural paradigm of the global society development on the basis of a categorial analysis of ideological foundations of the spiritual reality of social life. The author observes a disintegration of social life and proposes to stop it by means of cultivating the ideal meanings of social life and total expansion of a creative essence of spiritual culture in the historical practice of the mankind.
Keywords: Socio-cultural paradigm; spiritual reality; global social world; world of integrity; verbal-symbolic practices